(untitled) (Journal of the College of Basic Education, 2022)
The current study aimed to find out the effect of adding 10% oat powder to a mixture of minced meat tablets, in which chicken meat was replaced with pure veal meat, in five ratios of 100, 75, 50, 25.0%, on the physical and sensory characteristics of the processed meat tablets. Results showed The current study showed a significant increase in the percentage of losses during cooking by increasing the percentage of substituting chicken meat, and a significant decrease with the addition of 10% oats to the meat patties, by increasing the percentage of substituting chicken meat for pure veal meat.